1998
DOI: 10.1128/jb.180.23.6154-6163.1998
|View full text |Cite
|
Sign up to set email alerts
|

Catabolite Regulation of the Bacillus subtilis ctaBCDEF Gene Cluster

Abstract: Bacillus subtilis cytochrome c oxidase caa 3 is encoded by the ctaCDEF genes at the ctaABCDEF locus, with the ctaBCDEF genes organized as an operon-like unit. A dyad symmetry sequence and a catabolite response element homolog can be recognized in the 240-bp intercistronic region between ctaB and ctaC. ctaB-lacZ and ctaBCD-lacZ transcriptional fusions integrated at the native locus were used to study catabolite effects on transcription of the ctaB and ctaCDEF genes. In Schaeffer's medium lacking glucose, ctaBCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 43 publications
(72 reference statements)
0
22
0
Order By: Relevance
“…Our previous work showed that the ResDE two-component regulatory system regulates biofilm formation in B. amyloliquefaciens SQR9 (39), but the triggering environmental signal and the downstream molecular pathway remained unclear. Many studies have revealed the regulatory role of ResDE in both aerobic and anaerobic respiration in bacteria (40)(41)(42)(43)(44). Upon sensing a decrease in oxygen pressure, ResE activity changes from that of a phosphatase to a kinase, and it then transfers a phosphoryl group to the response regulator ResD; ResDϳP improves the transcription of targeted genes involved in the synthesis of heme-containing components of the electron transport chain (45).…”
mentioning
confidence: 99%
“…Our previous work showed that the ResDE two-component regulatory system regulates biofilm formation in B. amyloliquefaciens SQR9 (39), but the triggering environmental signal and the downstream molecular pathway remained unclear. Many studies have revealed the regulatory role of ResDE in both aerobic and anaerobic respiration in bacteria (40)(41)(42)(43)(44). Upon sensing a decrease in oxygen pressure, ResE activity changes from that of a phosphatase to a kinase, and it then transfers a phosphoryl group to the response regulator ResD; ResDϳP improves the transcription of targeted genes involved in the synthesis of heme-containing components of the electron transport chain (45).…”
mentioning
confidence: 99%
“…The main electron flow in glucose-grown B. subtilis is via the aa 3 oxidase (Santana et al, 1992) while the bd oxidase appears to be relevant mainly at low oxygen tension (Winstedt et al, 1998). The cytochrome c branch, which also contains the energy-coupling menaquinone:cytochrome c oxidoreductase (bc complex), is subject to catabolite repression and therefore undetectable in glucose-grown B. subtilis, but is expressed during growth on nonfermentable carbon sources (Liu and Taber, 1998;Yu et al, 1995). Thus, in glucose-grown B. subtilis, the maximum P/O appears to be 1 1 ⁄3, a value that compares very well with the overall respiratory H + /e − stoichiometry of 1.9 determined from oxygen pulse experiments with exponentially growing B. subtilis (Lauraeus and Wikström, 1993).…”
Section: Electron Transport Chain Composition In B Subtilismentioning
confidence: 99%
“…A conceptually simpler strategy would involve deleting the bd oxidases. Potentially adverse kinetic (Liu and Taber, 1998;Santana et al, 1992;Winstedt et al, 1998;Yu et al, 1995) and genomic database information (Kunst et al, 1997). The stoichiometry of energy coupling was estimated from the reported mechanisms of proton translocation (Trumpower and Gennis, 1994).…”
Section: Electron Transport Chain Composition In B Subtilismentioning
confidence: 99%
“…The ctaA and ctaB genes are required for heme A synthesis in B. subtilis [1,2]. These genes are located at 133° on the chromosome, immediately upstream of the ctaCDEFG gene cluster and ctaB is co‐transcribed with ctaCDEF [3].…”
Section: Introductionmentioning
confidence: 99%